(untitled) (Al-Qamar, 2024)
This study undertakes a comprehensive analysis of the critiques leveled against Islahi’s concept of coherence (nazm) in the Quran. Islahi’s concept posits that the Quranic chapters are coherent units, organized according to a specific thematic and structural logic. Through a critical review of existing literature, this research identifies and evaluates the key criticisms raised against Islahi’s concept, including issues related to textual interpretation, historical context, and literary analysis. The study aims to contribute to a deeper understanding of the complexities surrounding Islahi’s concept and its implications for Quranic exegesis. By examining the critiques of Islahi’s concept, this research seeks to inform and advance Quranic scholarship, ultimately enriching our understanding of the Quran’s structure, meaning, and significance.